Preparation and Properties of TiO2 Microparticles and its Composites with Polypyrrole - Zhao1, Haitao; Liu1, Ruiping; Liu2, Shaohong; Ma1, Ruiting (Asian Journal of Chemistry, 2014)
Spherical anatase TiO2 microparticles with good crystallinity were successfully synthesized by the homogeneous precipitation under mild conditions with ammonium fluorotitanate as the titanium source and urea as the precipitant. Then the TiO2 microparticles were used as nucleus for the preparation of TiO2/polypyrrole(TiO2/PPy) composite. TiO2/PPy composite was prepared by in situ polymerization of pyrrole on TiO2 microparticles. The structural characteristics, morphology and dielectric properties of the composite powders were obtained by X-ray diffraction, scanning electron microscope and network analyzer. The results show that TiO2 microspheres obtained in this work are anatase-type. The higher reaction temperature leads to smaller anatase microspheres. The morphologies of the final particles change into irregular with the increase of the reaction time. The e¢, e¢¢ and tande value for TiO2/PPy composite are higher than polypyrrole in the frequency range of 8.2-12.4 GHz. The tande value for TiO2/PPy has achieved a maximum of 0.57 at 11.9 GHz.